Failure analysis of P110 steel tubing in low-temperature annular environment of CO2 flooding wells. (February 2016) - Liu, Z.Y.; Li, H.; Jia, Z.J.; Du, C.W.; Li, X.G.
Abstract: In this study, the failure analysis of P110 steel in low-temperature annular environment of CO2 flooding wells is addressed. Results show that the chemical composition, microstructure, and mechanical properties (including tensile and impact properties) of the P110 steel tubing meet the standard requirements. According to the analysis of corrosion products, the annular environment contains CO2, Cl −, SO4 2 −, and a small amount of S 2 − (H2 S), which can induce stress corrosion cracking (SCC) in the presence of residual stress. The specimen fractures at the tubing, and the fractures are investigated by visual inspection, scanning electron microscopy, and energy-dispersive spectrometry. Three different areas are present on the fracture surface: the crack initiation area, crack expansion area, and the final fracture area. The fracture initiates from the Y-shaped corrosion cracks, which is accompanied by SCC characteristics. The reduction of ductility and toughness may also facilitate SCC of the tubing. Highlights: The failure of P110 steel under low-temperature annular environment of CO2 flooding wells has been observed. The SCC under low-temperature annular environment of CO2 flooding wells has been investigated. The SCC susceptibility under low-temperature/high-pressure environment is higher than high-temperature/high-pressure environment.